1982
DOI: 10.1111/j.1471-4159.1982.tb07989.x
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Transport of Choline Lipids in Normal and Regenerating Rat Sciatic Nerve

Abstract: Biochemical methods were used to study the time course of transport of choline phospholipids (labeled by the injection of [3H]choline into the ventral horn of the lumbar spinal cord) in rat sciatic nerve. Autoradiographic methods were used to localize the transported lipid within motor axons. Transported phospholipid, primarily phosphatidylcholine, present in the nerve at 6 h, continued to accumulate over the following 12 days. No discrete waves of transported lipid were observed (a small wave of radioactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Spencer and Thomas, 1974). Earlier studies have presented evidence that small molecules (, 1 kDa) of neuronal origin, such as phospholipids Gould et al, 1982;Ledeen et al, 1992;Toews et al, 1988), and nucleosides and polyamines Lindquist et al, 1985), can be transferred from the axon to the myelinsupporting glial cells under physiological conditions. Some types of invertebrate periaxonal glia also seem to have a rapid access to a variety of larger tracer molecules after their introduction into the neuron (Goldstein et al, 1982;Grossfeld, 1991;Grossfeld et al, 1988;Lieberman et al, 1994;Viancour et al, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…Spencer and Thomas, 1974). Earlier studies have presented evidence that small molecules (, 1 kDa) of neuronal origin, such as phospholipids Gould et al, 1982;Ledeen et al, 1992;Toews et al, 1988), and nucleosides and polyamines Lindquist et al, 1985), can be transferred from the axon to the myelinsupporting glial cells under physiological conditions. Some types of invertebrate periaxonal glia also seem to have a rapid access to a variety of larger tracer molecules after their introduction into the neuron (Goldstein et al, 1982;Grossfeld, 1991;Grossfeld et al, 1988;Lieberman et al, 1994;Viancour et al, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…Although the cytidine ("Kennedy") pathway is localized primarily in the endoplasmic reticulum (Wilgram and Kennedy, 1963), recent studies have demonstrated the presence in myelin of virtually all the enzymes needed to convert diacylglycerol to phosphatidylcholine and phosphatidylethanolamine (see Introduction). The existence of such enzymes in myelin had been suggested by earlier studies which indicated that certain substrates are transferred from the axon to myelin where they are incorporated in situ into specific lipids (Droz et al, 1978(Droz et al, , 1981Haley and Ledeen, 1979;Toews and Morell, 1981;Alberghina et al, 1982;Gould et al, 1982;Ledeen and Haley, 1983). The process was selective since other myelin lipids (e.g., gangliosides, sulfatides) appeared not to be labeled by this route (Haley and Ledeen, 1979), and the corresponding synthetic enzymes could not be detected (Wu and Ledeen, 1980).…”
Section: Resultsmentioning
confidence: 98%
“…A growing number of lipid-metabolizing enzymes, including several involved in phospholipid biosynthesis, have been shown to occur in purified CNS myelin (for review, see Suzuki, 1980;Norton, 1981; Norton and Cammer, 1984;Ledeen, 1984). The existence of such enzymes in myelin had been suggested by several studies (Droz et al, 1978, 198 1;Haley and Ledeen, 1979;Toews and Morell, 1981;Alberghina et al, 1982;Gould et al, 1982;Ledeen and Haley, 1983) indicating transfer of various substrates from the axon to myelin, these substances then becoming enzymatically incorporated into myelin lipids. We have previously shown myelin to possess CDP-ethanolamine: 1,2-diacyl-sn-glycerol ethanolaminephosphotransferase (EC 2.7.8.1) (Wu and Ledeen, 1980) and CTP:phosphoethanolamine cytidylyltransferase (EC 2.7.7.14) (Kunishita and Ledeen, 1984), the two enzymes that complete the synthesis of phosphatidylethanolamine.…”
Section: Departments Of Neurology and Biochemistry Albert Einstein Cmentioning
confidence: 91%